Determining the broodstock origin and pathogens occurrence in a giant freshwater prawn (Macrobrachium rosenbergii) nucleus breeding farm / Chong Khai En - Chong , Khai En (2019)
The giant freshwater prawn, Macrobrachium rosenbergii, as known as udang galah in Malaysia, is the biggest freshwater prawn in the world. The Department of Fisheries in Malaysia is giving priority on M. rosenbergii as food products for consumption and export. However, the major limitation in shrimp production is diseases. Like other animals, prawns are affected by viruses, bacteria, fungi, and metazoan parasites. A giant freshwater prawn nucleus breeding farm located in in Kampung Chennah, Jelebu, Negeri Sembilan has no systemic approach to prevent prawn diseases caused by viruses and bacteria. This study was undertaken to implement a systemic approach of genetic, health surveillance and biosafety measures in the farm. 19 juveniles M. rosenbergii (cycle 1) and 30 juveniles M. rosenbergii (cycle 2) were sampled from the pond by seining for mitochondrion DNA analysis, viral screenings and bacterial screenings. The first part of this study is useful to create a genetic profile of Macrobrachium rosenbergii and to know the origin of broodstock by using mitochondrion DNA analysis. Cytochrome c oxidase I (COI) of mitochondrial gene was used for phylogenetic analysis by DNA amplification using the Polymerase Chain Reaction (PCR) method. MEGA X software was used to construct a phylogenetic tree from the aligned sequences, followed by Network 5 software was used to generate a median-joining haplotype network. The haplotype network diagram generated shows the broodstock are come from four states which are Kedah, Perlis, Johor, Negeri Sembilan. The second part of this project is virus screening of M. rosenbergii from the farm. DNA viruses include White Spot Syndrome Virus (WSSV), Infectious Hypodermal and Hematopoietic Necrosis Virus (IHHNV), Monodon Baculovirus (MBV), Baculovirus penaei Virus (BP) and RNA viruses include Yellow Head Virus (YHV), Taura Syndrome Virus (TSV), Infectious Myonecrosis Virus (IMNV), Macrobrachium rosenbergii nodavirus (MrNV) were screened using multiplex PCR method. Dual priming oligonuclotide (DPO) primer was used to produce high PCR specificity by inhibiting mismatching and non-specific priming of the primers to the template under less optimal PCR conditions. The third part of this project is screening of Vibrio parahaemolyticus bacteria, which cause acute hepatopancreatic necrosis disease (AHPND) in giant freshwater prawn. Polymerase chain reaction was performed using primer AP3, which targets sequence 336 bp. All 19 juveniles M. rosenbergii collected from cycle 1 showed the absence of DNA viruses and RNA viruses. On the other hand, out of 30 juveniles M. rosenbergii collected from cycle 2, all showed the absence of DNA viruses, 5 samples show the presence of Yellow Head Virus (YHV) infection. The results showed the prevalence of YHV infection in prawn samples was 80%. The reasons for YHV infection in prawns could be contamination of broodstock, contamination of water supply and pond environment. For Vibrio parahaemolyticus screening, all samples show negative result. A systemic approach of biosafety measures is developed for the prawn farm to prevent diseases. These measures include prawn health surveillance, quarantine records, water quality monitoring, disinfection and hygiene, disease outbreaks investigation and standard operating procedures.